Mathematik im Kindergarten: Kritische Anmerkungen zu den neuen „Bildungsplänen“ für Kindertageseinrichtungen (mathematica didactica, 2007)
Curriculum documents for early childhood education in kindergarten, which have been recently released by all German states, highlight the importance of early childhood education prior to school and outline respective policy guidelines. In this context, early mathematics education at kindergarten level has attracted attention. Based on a review of the (historical) development of early numeracy approaches and policies, current documents are critically examined. In conclusion, the relevance of the new documents for teaching and learning early numeracy in kindergarten is being discussed followed by some suggestions for its development.